Drawings of Rembrandt (Vol.1) - Rembrandt, Harmenszoon van Rijn
The book gives an excellent idea of Rembrandt's unmatched range, depth, and human sympathy. It includes self-portraits and portraits; sketches of the humdrum activities on Amsterdam's busy streets; beggars and quacks, children at play, women gossiping, or people merely watching the paasing scene; studies of Jewish types and Orientals; drawings of nudes, birds, domestic animals and captive wild beasts; copies of famous works and art, rare medals and exotic Moghul miniatures; views of towns and architectural monuments; studies of the landscape around Amsterdam and of the spacious Dutch countryside; drawings of episodes from classical mythology, ancient history, and, above all, the Bible